Mobilizing funds for higher education through applying musharakah in waqf properties - Osmani, Noor Mohammad; Hoque, Muhammad Nazmul (Centre for Research on Islamic Banking & Finance and Business, USA, 2018)
Purpose- Integration of Waqf with any Islamic modes which can be financed to revive waqf property or make advancement in purpose of investment on different usage of Islamic modes for financing higher education using waqf properties. Therefore, the purpose of the study is to promote a model which can be a model based on Musharakah to finance the higher education. Designed/Methodology/Approach – This study adopts qualitative approach. It reviews and analyses contemporary data through relevant literatures and documents. Findings – Waqf played a significant role in providing financial assistance to the institutions and strengthening its academic quality. Many examples prove that the individual contributions are the main source of financing higher education. Recently many institutions have been using Endowment/Waqf as investment policy to raise fund for financing higher educational institutions. Therefore, waqf also could be used based on Islamic financial instruments as financial tools. The paper then discussed the integration of waqf based on Islamic financial products to raise fund for financing higher educational institutions. Finally; the paper establishes the values of sustainability and continued assets that will consistently benefit society at large, and educational institutions in particular, when the charity of waqf is well maintained. The paper thereby develops a system model of participatory interrelationship for the objective of attaining social wellbeing for the common good. Originality/Value – this article adds new knowledge by examining the waqf based Islamic financial products to raise the fund for financing higher educational institutions. It is expected that the instance of the investment of various waqf based financial instruments may contribute to find out an alternative source for the funding crises in contemporary institutions.